Pengaruh Metode Diskusi Manajemen Diklat Terhadap Pemahaman Mahasiswa Manajemen Pendidikan Islam C4 Angkatan 2022 - Ana Qonita; Betha Auldina; Muhammad Nuryan Firnanda; Asrof Abidin; Rofiq Hidayat (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study aims to investigate the influence of the Management Training Discussion Method on the Understanding of Islamic Education Management Students C4 Class of 2022. Discussion is an activity where people gather to talk and share opinions about a topic. The goal of the discussion is to broaden the understanding of a particular issue or topic. Training Management is the process of managing training within an organization. Its purpose is to enhance knowledge, skills, and abilities to work more effectively and efficiently. The method used in this research is a quantitative method, employing a causal-comparative approach with online questionnaires distributed through electronic media such as Google Forms. The findings from this study indicate that a constant variable does not contribute significantly to the correlation analysis, but it can still show a significant relationship in the regression analysis.